MEDAN MAKNA VERBA ‘MENYAKITI’ DALAM BAHASA SUWAWA - Darmawati MR (Kantor Bahasa Provinsi Gorontalo, 2016)
This paper discussed a verb to hurt in Suwawa language and knowing the components of the meaning of each verb. This paper used the framework meaning expressed by Lutzeire (1983), the theory of component analysis by Nida (1975), and the relation of a meaning theory proposed by Cruse (1987). This study was descriptive with qualitative approach. The data were collected by using the recording technique and interview. Based on data analysis, obtained 31 components of meaning or lexemes of Suwawa that can be classified into five parts, namely a); hurt by hand or arm; b) harm to foot; c) hurt by a sharp instrument/blunt; d) hurt by words. The lexemes form of the verb synonymous or have intersected meaning. This is consistent with what is stated by Chaer that the relationship between the superordinate and its hyponym or otherwise just easily seen on nouns, but rather difficult to see in the verbs and adjectives, while the meaning of the verb’hurt’, is a verb.